2002
DOI: 10.1046/j.1439-0272.2002.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of norethisterone and its A-ring reduced metabolites on the acrosome reaction in porcine spermatozoa

Abstract: The synthetic progestin, norethisterone (NET), has been reported as a contragestational postcoital agent in humans, rodents and rabbits. The effect and molecular mechanisms of NET and its A-ring reduced metabolites, 5alpha-NET and 3beta5alpha-NET, on the acrosome reaction (AR) are unknown. The aim of this study was to assess the effect of these compounds on an in vitro progesterone-induced AR in porcine spermatozoa. The spermatozoa were obtained from semen ejaculated by proven fertile adult pigs. Seminal plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our hormone binding experiments have shown that neither NET nor 5 α ‐NET are able to displace the binding to progesterone receptor (data no shown). This suggests that the effects observed in this study and in porcine spermatozoa (Martínez et al. , 2002) might have occurred through pathways different than that of the membrane progesterone receptor.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our hormone binding experiments have shown that neither NET nor 5 α ‐NET are able to displace the binding to progesterone receptor (data no shown). This suggests that the effects observed in this study and in porcine spermatozoa (Martínez et al. , 2002) might have occurred through pathways different than that of the membrane progesterone receptor.…”
Section: Discussionmentioning
confidence: 65%
“…In a previous study, we demonstrated the agonistic effect of norethisterone (NET) and the antagonistic effect of its A‐ring reduced metabolite 5 α ‐NET on the pig spermatozoa AR (Martínez et al. , 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation